Emotional intelligence, transformational leadership, and team satisfaction during the COVID-19 period in Belgium - Chevalier, Sabrina; Perot, Antoine; Klenkenberg, Sophie; Dumoulin, Florence; Declaye, Joséfine; Stipulante, Samuel; Ghuysen, Alexandre; Paquay, Méryl (Frontiers in Organizational Psychology, 2025)
IntroductionHealthcare crises such as the COVID-19 pandemic have intensified the need for effective leadership. While transformational leadership (TL) and emotional intelligence (EI) are known to support team resilience, little is known about how they interact in high-stress environments. Understanding this relationship is essential to improve leadership responses in future disruptions. This study explored the link between EI and TL during a crisis and examined how leadership profiles influenced team satisfaction with the interventions implemented.MethodsUsing a mixed-method, exploratory sequential design, the study included 209 participants (16 head nurses and 193 nursing staff) in Belgium. Interviews with head nurses identified key crisis interventions, which informed the development of a satisfaction questionnaire. In the quantitative phase, head nurses completed EI and TL assessments, while their teams rated satisfaction. Analyses were conducted using RCommander.ResultsEI and TL were positively associated. However, high TL scores did not consistently predict higher team satisfaction. Leaders with high EI more frequently used participatory strategies appreciated by staff, such as debriefings and team reflection tools.DiscussionIn crisis contexts, emotionally intelligent leaders appear better able to adapt their approach, combining structure and support. TL alone may not suffice to meet evolving team needs. These findings support targeted leadership development and call for further experimental studies to understand underlying mechanisms.